Outcomes of Reoperation After Acute Type A Aortic Dissection: Implications for Index Repair Strategy. Issue 10 (3rd October 2017) - Wang, Hanghang; Wagner, Matthew; Benrashid, Ehsan; Keenan, Jeffrey; Wang, Alice; Ranney, David; Yerokun, Babatunde; Gaca, Jeffrey G.; McCann, Richard L.; Hughes, G. Chad
Abstract : Background: The optimal surgical approach for management of acute type A aortic dissection remains controversial. This study aimed to assess outcomes of reoperation after acute type A dissection repair to help guide decision making around index operative strategy. Methods and Results: All aortic reoperations (n=129) at a single referral institution from August 2005 to April 2016 after prior acute type A dissection repair were reviewed. The primary outcome was 30‐day or in‐hospital mortality. Secondary outcomes included organ‐specific morbidity and 1‐ and 5‐year outcomes as estimated using the Kaplan–Meier method. The majority of initial reoperations were proximal aortic (aortic valve, aortic root, or ascending) or aortic arch procedures (62.5%, n=55); most initial reoperations were performed in the elective setting (83.1%, n=74). Additional nonstaged second or more reoperations were required in 21 patients (23.6%) after the initial reoperation, during a median follow‐up of 2.5 years after the initial reoperation. Thirty‐day or in‐hospital mortality for all reoperations was 7.0% (elective: 6.3%; nonelective: 11.1%) with acceptable rates of organ‐specific morbidity, given the procedural complexity. One‐ and 5‐year overall survival after initial reoperation was 85.9% and 64.9%, respectively, with aorta‐specific survival of 88% at 5 years. Conclusions: Reoperation after acute type A aortic dissection repair is associated with low rates of mortality and morbidity. These data support more limited index repair for acute type A dissection, especially for patients undergoing index repair in lower volume centers without expertise in extensive repair, because reoperations, if needed, can be performed safely in referral aortic centers.